Baby Massage and Baby Gym to Increase Infants Growth - Rose Nurhudariani; Gunarmi Gunarmi; Fery Agusman Mutoho Mendrofa (Jurnal SMART Kebidanan, 2022)
ABSTRACTInfancy is a golden period as well as a critical period of growth and development. The number of babies born in 2021 in Indonesia is 4,438,141 people and in the area of Central Java Province 508,062 live births, Semarang City the number of babies born is 22,030 babies. The cause of malnutrition is not only due to lack of consumption of nutrients, but also due to infection or disease. Baby massage can increase growth in babies if done correctly and regularly. The baby gym movement increases muscles and joints so that motor skills increase and will improve body function skills. The purpose of this study was to determine the effectiveness of baby massage and baby gym on the growth of babies aged 3-5 months in South Semarang District, Semarang City. Quasi-experimental research, Pretest-Postest control group design. The research sample was 32 infants, each group 16 babies. The research sampling technique uses purposive sampling. There is no significant difference in growth before and after treatment between the baby massage and baby gym groups, p-value ≥ 0.05, but baby massage is more effective for increasing baby growth compared to baby gym. Baby massage is more effective for increasing baby growth. growth. Baby's parents in increasing baby's growth by doing baby massage more often.Keywords: baby massage; baby gym; growth ABSTRAKMasa bayi adalah masa keemasan sekaligus masa kritis pertumbuhan dan perkembangan. Jumlah bayi lahir tahun 2021 di Indonesia 4.438.141 jiwa dan wilayah Provinsi Jawa Tengah 508.062 bayi lahir hidup, Kota Semarang jumlah bayi lahir 22.030 bayi. Penyebab gizi buruk bukan hanya disebabkan kurangnya konsumsi gizi, namun juga disebabkan karena infeksi atau penyakit. Baby massage dapat meningkatkan pertumbuhan pada bayi jika dilakukan dengan benar dan secara rutin. Gerakan baby gym meningkatkan otot dan persendian sehingga motorik meningkat dan akan meningkatkan keterampilan fungsi tubuh, Tujuan Penelitian ini adalah mengetahui efektifitas baby massage dan baby gym terhadap pertumbuhan bayi umur 3-5 bulan di Kecamatan Semarang Selatan, Kota Semarang. Penelitian quasi experiment, Pretest-Postest control group design. Sampel penelitian sebanyak 32 bayi, masing-masing kelompok. 16 bayi. Tehnik Sampling penelitian menggunakan purposive sampling. Hasil Penelitian: tidak terdapat perbedaan yang signifikan pertumbuhan sebelum dan sesudah perlakuan antara kelompok baby massage dan baby gym, p-value ≥ 0,05, tetapi baby massage lebih efektif untuk meningkatkan pertumbuhan bayi dibandingkan dengan baby gym  Simpulan: Baby massage lebih efektif untuk meningkatkan pertumbuhan. Orang tua bayi dalam meningkatkan pertumbuhan bayi dengan lebih sering melakukan baby massage.Kata kunci : baby massage; baby gym; pertumbuhan